Efgartigimod combined with steroids as a fast-acting therapy for anti-SRP immune-mediated necrotizing myopathy - Qiqi Peng; Xiaoping Yao; Sheng Chen; Xiaofeng Li; Feifei Lin; Zhangyu Zou (Frontiers in Neurology)
BackgroundImmune-mediated necrotizing myopathy (IMNM) is a rare autoimmune disease. Efgartigimod is a human IgG antibody Fc fragment, can enhance the degradation of IgG and thus may be a promising therapeutic agent for IMNM.MethodsAll three patients exhibited proximal muscle weakness and markedly increased creatinine kinase (CK) levels. Moreover, the myositis antibody profile revealed positive anti-signal recognition particle (SRP) antibodies in all of them. Muscle biopsy performed on the first patient confirmed IMNM. Eventually, all three patients were diagnosed with anti-SRP IMNM. The first patient initially received methylprednisolone via intravenous injection and then commenced efgartigimod therapy. The second and third patients were treated with a combination of methylprednisolone intravenous injection and efgartigimod. The efficacy of efgartigimod treatment was evaluated by observing the changes in CK values and the manual muscle testing (MMT) score. Safety assessments included adverse events and serious adverse events.ResultsFollowing one cycle of efgartigimod treatment (administered at a dosage of 10 mg/kg, once a week for a total of 4 injections in one period) in these three patients, CK values decreased by 79.30, 95.80, and 93.62%, respectively. Their MMT score increased from 232, 156, and 169 to 242, 258, and 229, respectively. Evidently, these three patients demonstrated significant improvement in muscle strength and decrease of serum CK levels after efgartigimod treatment. No serious adverse events were observed during the efgartigimod treatment.DiscussionEarly application of efgartigimod in combination with methylprednisolone for the treatment of anti-SRP-IMNM led to a substantial decrease in CK values and effectively improved muscle strength. Consequently, Efgartigimod may prove to be an effective and safe therapeutic option for IMNM.